2009
DOI: 10.4103/0019-5154.48980
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin, atherogenic lipids and glucose levels in patients with skin tags

Abstract: Aim:To investigate the relationship between serum leptin, atherogenic lipid and glucose levels in patients with skin tags and healthy controls.Materials and Methods:A total of 58 patients, with at least three skin tags, aged 24 to 85 years, and 31 healthy controls aged 30 to 70 years, were examined in the present study. The subjects in all the groups were selected with statistically similar Body Mass Index (BMI). Fasting concentrations of plasma glucose, serum lipids including triglyceride, total cholesterol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 15 publications
2
32
0
1
Order By: Relevance
“…These results are consistent with those of Sanlier [11] and other authors [13][14][15][16][17][18][19][20]. The correlation was consistent with that found by Ibrahim et al [21] and Ezam et al [22].…”
Section: Correlation Between Plasma Leptin Plasma Ghrelin and Bmisupporting
confidence: 83%
“…These results are consistent with those of Sanlier [11] and other authors [13][14][15][16][17][18][19][20]. The correlation was consistent with that found by Ibrahim et al [21] and Ezam et al [22].…”
Section: Correlation Between Plasma Leptin Plasma Ghrelin and Bmisupporting
confidence: 83%
“…A relationship between STs and diabetes mellitus has also been reported in a study conducted by Bahgat and Safory [23]. In a study conducted by Gorpelioglu et al, there was no difference for BMI and HbA1c levels [24].…”
Section: Discussionmentioning
confidence: 71%
“…Other studies have reported significant association of Leptin levels with STs [5,25,26]. But a recent Indian study did not find a significant association between Leptin levels and STs [24]. Association of BMI with ST was found in some studies [24,27].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bu da bize molluskum pendulum lezyonlarının varlığının yanı sıra fazla sayıda olmasının da glukoz toleransında bozulma için uyarıcı olması gerektiğini göstermektedir. Molluskum pendulum lezyonları olan hastaların karbonhidrat metabolizması ile ilişkili bir diğer parametre olan serum lipit düzeyleri açısından da değerlendirildiği ve aterogenik lipit profilinde bozulma olduğu ve bu hastalarda ateroskleroz ve kardiyovasküler hastalık riskinin arttığını belirten çalışmalar mevcuttur [20][21][22] . Çalışmamızda total kolesterol, trigliserid, HDL, LDL ve VLDL düzeyleri hasta grubu ve kontrol grubunda anlamlı farklılık göstermedi ancak molluskum pendulum sayısı ile total kolesterol ve trigliserid değerleri arasında doğru orantılı bir ilişki saptandı.…”
Section: Discussionunclassified